Fundamentación teórica de la tecnología en la educación (Journal of Parents and Teachers, 2014)
The article takes a look at the reasons that justify the use of technology in education. In this way, the contributions of behaviourism and constructivism to educational technology applications are analysed. Both theories share the same structure, favouring the organisation and processing of knowledge. This fact evidences the great contributions of the world of technology in education
Keywords: Technology; Education; Apps; Software